2019
DOI: 10.1177/1948550619841631
|View full text |Cite
|
Sign up to set email alerts
|

A Growth Mind-Set Intervention Improves Interest but Not Academic Performance in the Field of Computer Science

Abstract: We investigated whether a growth mindset intervention could be leveraged to promote performance and interest in computer science, through what mechanisms it might do so, and whether effects were stronger for women than for men. In particular, we explored whether the growth mindset intervention improved academic performance and career interest by increasing intrinsic value. We developed and tested a scalable, online, 4-session growth mindset intervention at 7 universities, across 16 introductory computer scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 48 publications
1
56
1
2
Order By: Relevance
“…Further studies will be necessary to better understand the differential effect of active learning on the academic performance of Latin@ and Black students. Prior studies have demonstrated the positive impact of messaging for helping students transition from a fixed to a growth mindset about their learning (Blackwell et al, 2007;Burnette et al, 2019). Yet in the present study, we did not observe a measurable change in students' growth mindset in response to DDP, even though this pedagogy helped us to eradicate or narrow performance gaps in our introductory biology courses.…”
Section: Discussioncontrasting
confidence: 84%
“…Further studies will be necessary to better understand the differential effect of active learning on the academic performance of Latin@ and Black students. Prior studies have demonstrated the positive impact of messaging for helping students transition from a fixed to a growth mindset about their learning (Blackwell et al, 2007;Burnette et al, 2019). Yet in the present study, we did not observe a measurable change in students' growth mindset in response to DDP, even though this pedagogy helped us to eradicate or narrow performance gaps in our introductory biology courses.…”
Section: Discussioncontrasting
confidence: 84%
“…Some of these interventions have benefited students-improving academic performance, increasing persistence in science, technology, engineering, and mathematics (STEM), and eliminating gender and racial achievement gaps (e.g., Blackwell et al, 2007;Good et al, 2003;Yeager et al, 2014Yeager et al, , 2019Fink et al, 2018). However, many attempts to replicate these benefits have failed to do so (e.g., Dommett et al, 2013;Sriram, 2014;Orosz et al, 2017;Burnette et al, 2020). In fact, two recent meta-analyses have raised questions about the strength of the link between mindset and academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, impacts of such interventions specifically in introductory programming courses have been mixed. A large-scale study that was published while we were in the middle of our study also failed to observe performance gains (or gender differences) from growth mindset interventions in introductory computing courses [5]. That paper also found what seems to be common in introductory programming courses: students have a pretty strong growth mindset orientation from the start.…”
Section: Why Didn't Non-cognitive Activities Help?mentioning
confidence: 48%
“…Another intervention conducted across multiple institutions also found no significant difference in the mindsets between experimental and control groups [37]. Notably, a recent, large, multi-institutional study on growth mindset interventions in C courses found that these interventions increased students' interest in CS but did not improve their performance [5].…”
Section: Background 21 Interventionsmentioning
confidence: 99%
See 1 more Smart Citation